2016
DOI: 10.1128/aac.02947-15
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Flow Cytometry Test for Identification of Different Carbapenemases in Enterobacteriaceae

Abstract: A flow cytometry test was developed to identify carbapenemase production by Enterobacteriaceae and to discriminate between the different types of carbapenemases (classes A, B, and D). It is based on the detection of meropenem activity against bacteria, coupled with different carbapenemase inhibitors, which is assessed by flow cytometry. It represents a convenient, fast, and reliable approach (100% sensitivity and 100% specificity) for the detection and characterization of different carbapenemases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…We previously described microbiological applications of FC, including susceptibility evaluation of antifungals, as well as the elucidation of antifungal resistance mechanisms (Pina-Vaz and Rodrigues, 2010 ). Moreover, we developed AST cytometric protocols regarding the main mechanisms of resistance to betalactams with the most important bacteria involved in clinical infections (Faria-Ramos et al, 2013 ; Silva et al, 2016 ). In this study we evaluate the performance of FASTinov ® kit for AST of Gram negative bacteria from positive blood cultures.…”
Section: Introductionmentioning
confidence: 99%
“…We previously described microbiological applications of FC, including susceptibility evaluation of antifungals, as well as the elucidation of antifungal resistance mechanisms (Pina-Vaz and Rodrigues, 2010 ). Moreover, we developed AST cytometric protocols regarding the main mechanisms of resistance to betalactams with the most important bacteria involved in clinical infections (Faria-Ramos et al, 2013 ; Silva et al, 2016 ). In this study we evaluate the performance of FASTinov ® kit for AST of Gram negative bacteria from positive blood cultures.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, this assay can be eventually compared with ceftazidime/avibactam combination (only with KPC or OXA-48-like enzymes) ( Chahine et al, 2015 ). Flow cytometry is an excellent tool, still unexplored in Microbiology, allowing to study antimicrobial activity ( Pina-Vaz et al, 2005 ; Pina-Vaz and Rodrigues, 2010 ) drug associations ( Teixeira-Santos et al, 2012 ), and mechanisms of resistance ( Faria-Ramos et al, 2013 ; Silva et al, 2016 ). Flow cytometric results showed that even at a low concentration and a short incubation time, a synergistic effect could be easily observed and quantified.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we studied the association between ertapenem and the other three carbapenems: imipenem, meropenem, and doripenem, against different types of carbapenemases producing by Enterobacteriaceae , belonging to Amber classe A, B, and D. Those drugs associations were studied by the time-killing kinetic curves as well as a new flow cytometry cell analysis. We have recently developed a protocol for identification of carbapenemases in 1 hour based on flow cytometry analysis ( Silva et al, 2016 ) with great accuracy. Additionally, a computational protein–ligand docking analysis allowed us to understand the molecular affinity of the different drugs regarding different enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…For each selected antibiotic concentration, a staining index (SI) was calculated as the ratio of fluorescence intensity of bacterial cells treated with antibiotic to that of non-treated cells. An increased median intensity of the green fluorescence (530/30 nm), of at least twice corresponded to dead bacterial cells (depolarized cells) [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…The standard AST methods based on the assessment of microbial growth inhibition include manual (e.g., disk diffusion, broth microdilution) and automated AST, such as the Microscan Walkaway (Beckman Coulter), Phoenix Automated Microbiology System (BD), and Vitek 2 (bioMérieux) [ 1 ]. Several analysis protocols based on flow cytometry (FC) were developed for microbial detection and species identification, as well as for AST and elucidation of antimicrobial resistance mechanisms [ 2 , 3 ]. The major advantage of using FC directly on clinical specimens is that it could provide early data on antibiotic susceptibility profiles, thereby allowing the implementation of an adequate empirical treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%